URBAN DESIGN International - Arefi, Mahyar; Nasser, Noha.; SpringerLink (Online service) (London : Palgrave Macmillan UK : Imprint: Palgrave Macmillan.)
URBAN DESIGN International is: an essential forum for the exchange of information and debate concerning issues of urban design and management a vital resource for urban designers, architects, planners, landscape architects and developers an international peer-reviewed publication. URBAN DESIGN International is the first truly international network for all of those involved in the multi-disciplinary tasks of urban design and management. In providing a direct forum for the exchange of information and a vehicle for the debate which constantly redefines the scope of urban design, the journal places a primary emphasis on bringing together practice and research. It addresses current issues and aims to make a range of materials accessible to all: from in-depth papers and reviews of projects, to book reviews, comments on previous contributions and a diary of international events. Some issues are themed by topic or geographic region. The international range of the journal is impressive as witnessed by contributions from all the major continents and an active and extensive editorial structure. Amongst the issues the journal addresses are: urban design urban development and management urban ecology transportation and highway design heritage and local identity diverse communities of interest.
Keywords: Architecture; Urban planning; City planning; Architecture, general; Cities, Countries, Regions; Urbanism